A retrospective study of cases of canine demodicosis submitted to a commercial diagnostic laboratory servicing the United Kingdom and Ireland (2017–2018) part 2; Aerobic culture and antimicrobial susceptibility results. (31st December 2022) - Kelly, Pamela A.; McKay, Jennifer S.; Maguire, David; Jones, Matthew; Roberts, Larry; Powell, Frank; Breathnach, Rory
Abstract: Clinical diagnostic reports from 508 cases of canine demodicosis diagnosed either by histological or skin scraping analysis from a United Kingdom Accreditation Service (UKAS) accredited veterinary diagnostic laboratory servicing the United Kingdom (UK) and Ireland were evaluated. Of the 508 cases, 284 had skin swabs submitted for culture on the same day the skin biopsy and/or skin scraping were obtained. Dogs with juvenile-onset (JO) demodicosis represented 57.4% of these cases, whilst adult-onset (AO) cases comprised 42.6%. The data revealed that overgrowth of pathogenic bacteria was more common in AO demodicosis cases (75.2%) in comparison to the JO cases (57%). Adult-onset cases also had increased involvement of bacteria belonging to multiple genera and/or yeast (28.9%) in comparison to JO cases (18.4%). Pruritus was significantly associated with an overgrowth of Staphylococcus pseudintermedius ( p <   0.001 ). Resistance to one or more antimicrobial classes was noted in S. pseudintermedius isolates from 56.3% of JO cases with 10.3% of these cases being classified as Multi-Drug Resistant (MDR). Similarly, 51.9% of S. pseudintermedius isolates from the AO cases were noted to be resistant to one or more antimicrobial class with 8.6% of these cases being considered MDR. Cephalosporins were the most frequently administered antimicrobial class noted in submission histories, followed by the penicillin and fluoroquinolone classes. Whilst our findings reveal a high prevalence of concurrent overgrowth of pathogenic bacteria warranting therapeutic intervention in canine demodicosis, the presence of resistance within isolates highlights the need for prudent selection and targeted use of antimicrobial therapy that encompass the key principles of antimicrobial stewardship. Highlights: Overgrowth of pathogenic bacteria was more common in AO demodicosis cases in comparison to the Juvenile Onset cases. AO cases also had increased involvement of bacteria belonging to multiple genera and/or yeast in comparison to JO cases. Pruritus was significantly associated with an overgrowth of Staphylococcus pseudintermedius (p < 0.001).